Application of AHP Method in Determining Bank Selection for Account Opening - Supriatin; Adelia Alvi Yana; Setiaji; Astrilyana (Institute of Computer Science (IOCS), 2022)
Banks are business entities that collect public funds as a place to carry out various financial-related transaction activities that people generally use to save money. Saving or saving money is an activity to set aside a portion of income for future needs. There are many kinds of banks in Indonesia that offer all the advantages ranging from administration to the interest given to customers. Decision Support System (DSS) is one of the decision-making methods that can assist a person in making accurate and targeted decisions. Many problems can be solved by using SPK, one of which is determining the selection of the best bank for account opening. Therefore, the author will examine and compare several bank names and bank criteria needed by prospective customers to open a new account. Data was collected by means of observation, interviews and literature study. It is hoped that this writing and research can add insight to anyone. The method used in this research is the Analytical Hierarchy Process (AHP) method. Analytical Hierarchy Process (AHP) is a method of decision support system by using a hierarchy and making comparisons on each criterion and alternative that is considered in decision making. It is very important in choosing a bank because the better the facilities and types of services provided by the bank, the greater satisfaction with the customer. In this study, the authors compare four banks that are widely chosen by the general public, namely Mandiri, BCA, BRI and BNI with four selection criteria including Administration, Interest, Transaction and Investment Limits located in the Greater Jakarta area (Jakarta Bogor Depok Tangerang Bekasi).